Low Temperature Phase Transitions During Cryopreservation of Horse Red Blood Cells Using Combined Cryoprotective Media - Ulizko, Pavlo Yu.; Bobrova, Olena M. (Problems of Cryobiology and Cryomedicine, 2017)
Probl Cryobiol Cryomed 2017; 27(2):178.